DDBD ozone plasma reactor generation: the proper dose for medical applications. (May 2019) - Azam, M; Restiwijaya, M; Zain, A Z; Sumariyah, S.; Setiawati, E; Richardina, V; Hendrini, A R; Dayana, B; Kinandana, A W; Arianto, F; Bintang, K N; Putri, Y; et al.
Abstract: Double Dielectric Barrier Discharge (DDBD) ozone plasma reactor generation are presented in this paper. The generation of this reactor generates ozone concentration which can be arranged upon the proper dose for medical applications. AC high voltage is applied to the range of 0-3 kV and the frequency of 50 Hz. Pure oxygen gas was piped into the DDBD reactor with flow rate variations of 2, 4 and 6 L/min. The results showed that current as a function of voltage where the current is increased with the increasing of voltage. Ozone productivity is shown by the significant increase of current. Ozone concentration is increasing as the increase of the voltage provided, but rather the concentration of ozone is decreasing as the increasing of flow rate. The Ozone capacity is affected by ozone concentration and flow rate, and can be used to determine the ozone dose. The proper dose of ozone can be ozone therapy for various kinds of diseases.